The use of an enzyme preparation when using calcium acetate in wheat bread technology - Bilyk, Olena; Kochubei-Lytvynenko, Oksana; Bondarenko, Yulia; Chernyushok, Olha (Technology audit and production reserves, 2019)
An important problem of bakery is the prevention of the main causes of spoilage of bread, namely the development of microorganisms, which, under favorable conditions, become activated and lead to complete unsuitability of the product for consumption. The spores of bacteria of the group of potato sticks are quite resistant to thermal effects, they remain viable even at temperatures close to 130 °C, but are sensitive to an acidic environment. The use of calcium acetate in the recipe of wheat bread to carry out a booming effect on microorganisms will also affect the quality of products. To improve the quality of such products, it is advisable to use amylolytic enzymes to intensify the fermentation of the dough and oxidative additives to reduce its stickiness and spreading. The object of research in the work is dough made from wheat flour of the first grade, the formulation of which includes calcium acetate, the enzyme preparation Alphamalt V and ascorbic acid. It is established that from the point of view of influencing the quality of finished products, a rational dosage of calcium acetate is 0.3 % by weight of flour. The optimal dosage of the enzyme preparation Alphamalt V is 0.015 % by weight of flour and ascorbic acid – 0.006 %. It is proved that the introduction of this composition of food additives improves gas removal ability by 15...20 % compared with the control and products containing only calcium acetate. The positive effect of the use of an enzyme preparation of amylolytic action along with calcium acetate on the lifting force of yeast has been established. This helps to intensify the fermentation of the dough and increase the specific volume and porosity of wheat bread. It is established that the use of a composition of food additives positively affects the elastic-elastic properties of the dough: the spreading of the dough balls decreases and the gas-holding ability increases by 10...13 % compared with products from calcium acetate. This leads to an increase in the specific volume and shape stability of bread. Thanks to the developed composition of food additives, it is possible to use calcium acetate to inhibit potato sticks without losing the quality of the finished product.